BUILDING ENVIRONMENTAL AWARENESS AMONG STUDENTS IN POLAND – CASE STUDY WROCŁAW UNIVERSITY OF SCIENCE AND TECHNOLOGY - Magdalena WĘGLARZ (Humanities and Social Sciences)
Climate change is one of the most important challenges facing our community today. Among its various sources, irresponsible human activity, including excessive consumption, plays a significant role. As a society, we compensate for periods of deprivation with increased consumption of many goods without regard for environmental effects. In this context, environmental consciousness, especially among young people forming their habits and attitudes, becomes extremely important. Generation Z, current university students, has demonstrated a notable increase in environmentally conscious actions and attitudes. The purpose of the article is to assess the state of environmental awareness and knowledge among Generation Z and to identify the activities of universities in building environmental awareness among students at Wroclaw University of Science and Technology (WUST). The article analyzes research conducted in Poland on environmental awareness and behavior among different groups of respondents. These findings were juxtaposed with the expectations of environmental education in Poland, noting that there is a lack of content related to environmental education and building environmental awareness in the study programs, which is due to the lack of a holistic approach to the entire process of environmental education. The article presents pro-environmental activities in the example of WUST. These activities mostly focus on the transfer of knowledge and somewhat less on motivating students to action. There is a lack of activities that build emotional involvement, which is crucial in developing environmental awareness. In addition, there is little involvement in social issues.